The influence of levodopa on respiratory function in Parkinson's disease patients: a systematic review and meta-analysis (Research, Society and Development, 2021)
There is no consensus in the literature about the influence of levodopa on respiratory disorders, which are the main cause of death in Parkinson’s disease patients. Thus, the aim of this study was to conduct a systematic review and meta-analysis to assess the influence of levodopa on lung function in patients with Parkinson’s disease. A systematic search was performed in the MEDLINE-PubMed, Lilacs, IEEE Xplore Digital Library and Cochrane Library databases, until July 2020. Eligibility, screening, data extraction and quality assessment of the studies found were conducted independently by a minimum of two reviewers. The meta-analysis was made using RevMan 5, using standardized difference of means (SDM) with the random effects model and 95% confidence interval. The presence of heterogeneity was evaluated through the percentage of i². In total, 78 studies were identified; of these,7 were included in the review and meta-analysis after considering the inclusion and exclusion criteria. By comparing the 'on' and 'off' levodopa states, in the outcomes of interest found in the included studies, the following results were obtained in the meta-analysis: FVC (SMD of 0.12, p = 0.41); FEV1 (SMD of 0.10, p = 0.47); PEF (SMD of -0.00, p = 0.99); FEV1/FVC (SMD 0.04, p = 0.76). The conducted study suggested that there was no influence of levodopa treatment on any of the pulmonary variables assessed in patients with Parkinson’s disease.